Two-Stage Energy Economic Optimal Dispatch of Virtual Power Plant in Deregulated Electricity Market - Lihang ZHAO; Weiguang CHANG; Min YANG; Qiang YANG; Ganghua QIN (Zhongguo dianli)
With the increasing penetration of renewable distributed energy resources (DER) in power grids, virtual power plant (VPP) as an effective management technology of DERs has attracted widespread attentions. In this paper, a two-stage energy economic optimal scheduling method is proposed for VPP in a deregulated electricity market, which consists of day-ahead stage and intra-day stage. In the day-ahead stage, the optimal scheduling plan for the next day is formulated based on the forecasting information, and an agreement is signed with the day-ahead electricity market organizer. In the intra-day stage, on the basis of the day-ahead scheduling plan, the model predictive control (MPC) strategy is used to adjust the intra-day operation plan so as to eliminate net load variation caused by forecasting errors as well as to minimize penalties from the intra-day balancing market, thus reducing the overall operation costs. The proposed models are solved by the commercial solver Gurobi 9.1. Numerical simulation results show that the proposed method improves the utilization rate of DER and equipment inside VPP by means of day-ahead scheduling and intra-day redispatching, which is economical and practical, and provides a new approach for the economic dispatch of VPP.